Incorporation of surface plasmon resonance with novel valinomycin doped chitosan-graphene oxide thin film for sensing potassium ion - Zainudin, Afiq Azri; Yap, Wing Fen; Yusof, Nor Azah; Al-Rekabi, Sura Hmoud; Mahdi, Mohd Adzir; Sheh Omar, Nur Alia (Elsevier, 2018)
In this study, the combination of novel valinomycin doped chitosan-graphene oxide (C–GO–V) thin film and surface plasmon resonance (SPR) system for potassium ion (K⁺) detection has been developed. The novel C–GO–V thin film was deposited on the gold surface using spin coating technique. The system was used to monitor SPR signal for K⁺ in solution with and without C–GO–V thin film. The K⁺ can be detected by measuring the SPR signal when C–GO–V thin film is exposed to K⁺ in solution. The sensor produces a linear response for K⁺ ion up to 100 ppm with sensitivity and detection limit of 0.00948° ppm⁻ᴵ and 0.001 ppm, respectively. These results indicate that the C–GO–V film is high potential as a sensor element for K⁺ that has been proved by the SPR measurement.